Solanum incanum extract enhances wound healing and tissue regeneration in burn mice model (Bangladesh Journal of Pharmacology, 2019)
This study was conducted to evaluate the topical efficacy of Solanum incanum for the treatment of partial-thickness burn in mice model. Mice were treated with topical ointment of S. incanum three times daily for 14 days. The wound healing was observed through wound contraction and histological parameters. The group treated with S. incanum ointment showed 81% reduction in wound area as compared to negative control where wound area reduced to 22%. The histological analysis further confirmed that ointment favors the tissue regeneration and reepithelization thus heal wound rapidly as compared to other groups. In conclusion, S. incanum extract enhances wound healing and tissue regeneration.Video clip of Methodology:Partial thickness burn:  2 min 1 sec   Click to watch